Phase prediction in high entropy alloys – A kinetic approach. (July 2018) - Chattopadhyay, C.; Prasad, Anil; Murty, B.S.
Abstract: A simple and completely predictive model has been developed to predict whether a multicomponent equiatomic alloy will form a single phase BCC, FCC, HCP or a combination of two or more solid solution phases or intermetallic compounds (IM) or an amorphous phase. This approach is based on the viscosity of alloys as a function of temperature, utilising the viscosities of its constituting elements, and suitably incorporating the crystal structure information. Some other parameters affecting viscosity of an alloy like atomic size of constituting elements, packing density of the unit cell, etc., are suitably incorporated into the model. The temperature-time-transformation (TTT) diagrams were generated with the help of the viscosity data of five widely experimentally examined alloys, CoCrCuFeNi, CoCrFeMnNi, AlCoCrFeNi, AlCuMgMnZn and ZrTiCuNiBe. The chance of formation of preferable lower order alloys has also been considered. In this regard, all the possible binary to quinary alloys that can form from the constituting elements have been studied. The formation of the single phase BCC, FCC, or formation of multi phases, IMs or an amorphous phase in these alloys has been excellently predicted by the model. It has also been revealed that AlCuMgMnZn alloy prefers to form a number of IMs with a rare HCP phase, which matches excellently with the experimental evidence. The most important part of the present work is that it acts as an efficient guide about the processing route that should be used to form an intended phase in a particular alloy via the critical cooling rate R c obtained through the predicted TTT diagrams. Further, two alloys (AlCoCrFeNi and CoCrFeMnNi) could not be vitrified even via melt spinning route as predicted by the model. Almost all the equiatomic alloys found so far ranging from ternary to octanary according to literature have been studied by the present model. The phase formation in most of the alloys has been predicted correctly by the model. Graphical abstract: Image 1